Pengaruh Kompensasi dan Pelatihan Terhadap Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan (Studi Pada PT. Ganesha Abaditama) - Putra, Aditya Ganesha; Suharnomo, Suharnomo (Diponegoro Journal of Management, 2017)
In order to achieve the maximum benefit, it is very important to acompany to pay attention about compensation and training to improve the performance of the employees. The Employees who receive compensation as they expect would directly be able to improve their performance. As well as the training provided, training whom appropriate to job would enhance the ability of these employees, so that the performance would also increase.This research was conducted at PT. GaneshaAbaditama located in East Jakarta in order to determine the effect of compensation and training on job satisfaction in improving employee performance. The samples are 65 respondents using census method. As the independent variable in this research are compensation and training, intervening variable is job satisfaction, as well as the dependent variable is the performance of employees. The analysis includes the validity, reliability, model test, classic assumption test, test hypotheses.The influence of compensation on job satisfaction is about 0.069, which means that compensation has a positive and significant relationship to job satisfaction. The influence of training on job satisfaction is about 0.351, which means that training has a direct influence on job satisfaction. The influence of compensation to the performance is about 0.010 indicates that proves compensation has no direct influence on the performance. The influence of training on the performance is about 0.272, which means that the effect of job satisfaction tested positive for performance. The influence of job satisfaction on the performance is about 0.589, which means that job satisfaction has a direct influence on the performance.